Exercise for Pain Relief in Yoga is Effective in Reducing Pelvic Girdle Pain During the Third Trimester of Pregnancy - Sri Sukamti; Aticeh Aticeh; Gita Nirmala Sari (Women, Midwives and Midwifery, 2022)
Background: Pelvic girdle pain (PGP) is one of the most common pelvic pains during pregnancy. PGP often occurs in pregnant women with an incidence of around 25?. Several methods have been developed to relax muscles or ligaments that can alleviate pelvic pain. Purpose: This study aimed to determine the effectiveness of exercise for pain relief in yoga in reducing pelvic girdle pain during the third trimester of pregnancy. Methods: This was a non-randomized controlled experimental study of 50 pregnant women in the third trimester with pelvic pain. The study was conducted in an antenatal clinic that provides prenatal yoga class. The treatment group (25 pregnant women) was given prenatal yoga for 2 weeks and the control group was provided with regular prenatal care. The level of pain was measured using a visual analog scale (VAS) with score from 0 to 10 before and after 2 week-prenatal yoga was given. Results: The level of pelvic pain was lower in the treatment group that was given prenatal yoga for pain relief. The mean value of pelvic pain before intervention was 4.36 and after intervention was 2.08. The two groups had different scores for pelvic pain (p value =0.000 and mean difference -2.28). There was a significant effect of prenatal yoga for pelvic pain relief on the intervention group. The mean difference was -2.130 (95%CIs=-2.583, -1.657), p value was 0.000. Conclusion: Exercise for pain relief in yoga was effective in reducing pelvic girdle pain during the third trimester of pregnancy. Pregnant women with pelvic girdle pain may practice a combination of regular pregnancy exercise and prenatal yoga to lessen the pain.